Volatile compounds and antifungal activity of Dracocephalum moldavica L. at different phenological stages. Issue 1 (2nd January 2022) - Abbasi, Nesa; Fattahi, Mohammad; Ghosta, Youbert; Sefidkon, Fatemeh
ABSTRACT: The present work aimed to study the essential oil (EO) variation of Dracocephalum moldavica L. under different phenological stages. The EO yield was highest in the flowering stage, followed by floral budding, fruit set, and vegetative stages. Twenty-three components in EOs were identified by GC-MS and quantified using GC-FID. Geranyl acetate (31–50 %), geranial (16–27 %), geraniol (12–13.4 %) and neral (10.67–17.30 %) were four main constituents. Antifungal assays of EO through mycelial growth inhibition percentages (MGI %) with four concentrations (0, 250, 500, and 750 µl/l) showed concentration-dependent responses. EOs showed the high potential of antifungal activity with ID50 values of (89–145), (27–88) and (183–339) µl/l and ID90 values of (667–1293), (509–1296), and (389–866) µl/l for Aspergillus niger, Penicillium expansum, and Trichoderma harzianum respectively. EO of D. moldavica showed considerable promise as a natural bio-preservative and bio-antifungal agent.